Chronic Isolated Fracture of the Metatarsal Head in Lesser Toes Treated with Open Reduction and Internal Fixation - Wenjing Li MD; Ying Li MD (Foot & Ankle Orthopaedics)
Category: Lesser Toes; Trauma Introduction/Purpose: Isolated fractures of a metatarsal head in the lesser toes are uncommon in clinical practice and are prone to being overlooked, potentially leading to chronic fractures or mal-union. This study aims to report the clinical and imaging characteristics, as well as treatment results, of these fractures. Methods: A retrospective consecutive case-series study was performed on 5 patients with symptomatic chronic isolated shear fracture of a metatarsal head in the lesser toes from January 2018 to April 2021. There were 4 males and 1 female, with a mean age of 26.2±6.7(range, 19-36) years at the time of surgery. Two of them (40%) were not diagnosed initially. The main symptom was limited dorsiflexion of the MTPJ. Preoperative X-rays and CT scans revealed dorsal displacement of the fragment without dislocation of the MTP joint.All patients were operatively treated using open reduction and internal fixation (ORIF). The American Orthopaedic Foot & Ankle Society-lesser metatarsophalangeal-interphalangeal (AOFAS-LMI) score, visual analog scale (VAS) score, and passive dorsiflexion range of motion (ROM) of the metatarsophalangeal joint (MTPJ) were determined preoperatively and at final follow-up. Postoperative complications were also recorded. Results: All of the chronic fractures achieved union. At the final follow-up (mean, 27.8±15.5 months; range 6-45), the mean AOFAS-LMI scores was 90.6±8.4 (range, 82 - 100) points, the median VAS score was 0 (range, 0 - 2.0) points, and the median MTPJ passive dorsiflexion ROM was 40.0 (range, 35 - 45) degree, which were improved compared with preoperatively [(70.6±7.4) (range, 59 - 79) points, 4.0 (range, 2.0 - 5.0) points, 10.0 (range, 5.0 - 10.0) degree, respectively)]. All patients returned to their respective preinjury activity levels. Three patients developed metatarsophalangeal joint arthritis. Conclusion: Patients with a chronic isolated shear fracture of a metatarsal head in the lesser toes treated by ORIF achieved good short-term and mid-term clinical outcomes. Figure 1 The male patient, aged 27, fell from a height of 1.5 meters, resulting in injury with a duration of 6 months. He complained of localized obscure pain in the right fourth metatarsophalangeal joint, with restricted dorsiflexion. Plain radiograph revealed narrowing of the fourth metatarsophalangeal joint space and overlapping shadows between the base of the proximal phalanx and the metatarsal head (A); oblique radiograph showed dorsal displacement and angular deviation of the fracture fragment, with loss of normal joint morphology (B); CT imaging demonstrated dorsal displacement of the metatarsal head fragment (C); physical examination indicated restricted dorsiflexion of the metatarsophalangeal joint (D); intraoperatively, a dorsal approach to the metatarsophalangeal joint was utilized (E); exposure revealed fracture of the metatarsal head, with dorsal displacement and deformity (F); osteotomy was performed along the original fracture line, and the fracture fragment was temporarily removed for debridement (G); fracture reduction was achieved, followed by temporary fixation with two Kirschner wires (H); definitive fixation was accomplished using a headless compression screw (I); the incision was closed layer by layer (J); manual manipulation confirmed full range of motion and smooth movement of the metatarsophalangeal joint (K); intraoperative fluoroscopy with a C-arm machine showed satisfactory reduction and optimal screw positioning (L, M); postoperative radiographs at 6 weeks (N, O) demonstrated fracture healing; at the final follow-up, anteroposterior (P) and lateral (Q) radiographs showed excellent fracture consolidation with mild signs of arthritis.